The relationship between clinical competence and compassion fatigue among emergency department nurses in Urmia hospitals in 2024 - Reza Abdollahi; Yousef Mohammadpour (حیات, 2025)
Background & Aim: Clinical competence may influence the level of compassion fatigue experienced by nursing staff. This study aimed to determine the relationship between clinical competence and compassion fatigue among emergency department nurses. Methods & Materials: This descriptive-analytical study was conducted among nurses working in the emergency departments of teaching hospitals in Urmia in 2024. A total of 120 nurses were randomly selected for participation. Data collection was performed using three questionnaires: a socio-demographic characteristics questionnaire, Leo’s Clinical Competence Questionnaire, and Figley's Professional Quality of Life Scale. Data analysis was performed using the Chi-square test and Pearson correlation coefficient with SPSS version 23. Results: The results showed a significant inverse relationship between clinical competence and compassion fatigue (r=-0.45; P<0.05). The mean score of clinical competence among participants was 201.13±0.54. The average scores for compassion fatigue, compassion satisfaction, and secondary traumatic stress were 27.73±8.54, 38.73±1.81, and 28.45±4.82, respectively. Conclusion: The results suggest that higher levels of clinical competence are associated with lower levels of compassion fatigue among emergency nurses. To mitigate compassion fatigue, nursing administrators and policymakers should consider implementing targeted strategies, such as comprehensive training, ongoing in-service education, and staffing with experienced and specialized nurses, thereby fostering a supportive work environment that reduces compassion fatigue.